2014
DOI: 10.15665/rp.v12i1.155
|View full text |Cite
|
Sign up to set email alerts
|

El aceite de palma africana elae guineensis: Alternativa de recurso energético para la producción de biodiesel en Colombia y su impacto ambiental

Abstract: El aceite de palma africana elae guineensis: Alternativa de recurso energético para la producción de biodiesel en Colombia... El aceite de palma africana RESUMENEn Colombia, la contaminación atmosférica generada durante la quema de combustibles fósiles, es uno de los principales problemas ambientales causante del deterioro de la calidad del aire, lo cual impacta negativamente al medio ambiente y la salud humana. Actualmente, la preocupación mundial por la protección del planeta, originó la necesidad de buscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…These emissions are mainly the result of the following types of activities carried out by the company: -Generation of electricity, heat or steam -Physical or chemical processesTransport of materials, products, waste and employees [5].…”
Section: Emission Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…These emissions are mainly the result of the following types of activities carried out by the company: -Generation of electricity, heat or steam -Physical or chemical processesTransport of materials, products, waste and employees [5].…”
Section: Emission Sourcesmentioning
confidence: 99%
“…The largest producers are Indonesia and Malaysia, which accumulate approximately 85% of the world supply. The Greenhouse gas emissions associated with processing of palm oil biodiesel are mainly caused by the discharge of 90% of the effluent from oil mills with high chemical oxygen demand (COD) values, which emit large amounts of methane [5].…”
Section: Introductionmentioning
confidence: 99%
“…land, without allowing the growth of any other activity around it, despite this, the cultivation of African palm is a friendly alternative to the environment to produce fuel. It is expected that the cultivated areas reduce emissions causing less greenhouse effect, depending on land use [20]. Likewise, the expansion of the agricultural frontier also produces environmental impacts evidenced in the research of Müller et al (2014) [21] where it was identified that in Bolivia, technified agriculture was responsible for 30% of forest loss, while small farmers were responsible for 18%.…”
Section: Environmental Impact Of Crop Development (Harvest)mentioning
confidence: 99%
“…Colombia el biodiesel es una alternativa para los combustibles de origen fósil, en la producción de energía para cubrir los requerimientos nacionales y movilidad. (14) , Siendo este un material biodegradable, renovable, no tóxico, cuya ignición proporciona bajos niveles de gases de efecto invernadero como CO 2 , NOx, SOx y material particulado (MP) (15) , es por ello que la investigación tiene como objetivo evaluar las características del aceite obtenido del fruto de Attalea butyracea como alternativa para la obtención de un aceite tipo biodiesel.…”
Section: Introductionunclassified